2020
DOI: 10.1111/jfpp.14942
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium release behavior from W/O/W emulsions incorporated into yogurt: Application to food supplementation

Abstract: Because of bad change in eating habits, our food becomes unbalanced and not diversified. For that purpose, a new concept appeared, is that of "functional food" whose purpose is to fortify food products by adding new ingredients or more of existing ingredients (e.g., trace elements, vitamins, …), in order to prevent the onset of certain diseases related to deficiency of these elements. These foods are similar in appearance to conventional foods and are meant to be consumed as part of a normal diet. They can hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
(65 reference statements)
0
4
0
Order By: Relevance
“…PGPR is widely known as an excellent lipophilic emulsifier (Bastida‐Rodríguez et al., 2013; Mortensen et al., 2017). It can be used alone or blended with other emulsifiers in W/O or W/O/W emulsions for potential food applications, such as the production of low‐fat spreads (Cofrades et al., 2014; Eisinaite et al., 2017; Freire et al., 2016; Serdaroğlu et al., 2016), as well as the encapsulation and delivery of active ingredients (Aditya et al., 2015; Herzi & Essafi, 2020; Santos et al., 2015; Zhu et al., 2016). Additionally, PGPR can be used in chocolate industry, particularly for improving the rheological properties, attenuating fat bloom, and increasing the tolerance to the thickening effect (Bastida‐Rodríguez et al., 2013).…”
Section: Functional Properties Of Pgprmentioning
confidence: 99%
See 2 more Smart Citations
“…PGPR is widely known as an excellent lipophilic emulsifier (Bastida‐Rodríguez et al., 2013; Mortensen et al., 2017). It can be used alone or blended with other emulsifiers in W/O or W/O/W emulsions for potential food applications, such as the production of low‐fat spreads (Cofrades et al., 2014; Eisinaite et al., 2017; Freire et al., 2016; Serdaroğlu et al., 2016), as well as the encapsulation and delivery of active ingredients (Aditya et al., 2015; Herzi & Essafi, 2020; Santos et al., 2015; Zhu et al., 2016). Additionally, PGPR can be used in chocolate industry, particularly for improving the rheological properties, attenuating fat bloom, and increasing the tolerance to the thickening effect (Bastida‐Rodríguez et al., 2013).…”
Section: Functional Properties Of Pgprmentioning
confidence: 99%
“…Besides, W/O and W/O/W emulsions can be used as carriers for a number of food ingredients to induce a controlled release or provide protection, that is, capsules loaded with ingredients, such as bittern (MgCl 2 ) in tofu and yogurt (Herzi & Essafi, 2020; Li et al., 2014; Zhu et al., 2016), and menthol and xylitol in chewing gum (Santos et al., 2014, 2015), or curcumin and catechin in beverage systems (Aditya et al., 2015). The results indicated that the emulsion systems exhibited a satisfactory controlled release and protection.…”
Section: Functional Properties Of Pgprmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of ice cream, the fat content is 10% to 12%, which can be replaced up to 80% by various oligosaccharides (as prebiotics) using DE (Yildirim et al, 2016;. Also, the phase of incorporation of bioactive compounds in DE affects the sensory characteristics and stability of the dairy product, since controlled release and better masking is possible offering better sensory characteristic of the product (Herzi & Essafi, 2020). Simiqueli et al (2019) demonstrated that the insertion of iron sulfate (FeSO4) in the internal phase of DE (W1) in a milk dessert increases the sensory perception of undesirable changes, while the insertion in the external phase (W2) allows the addition of higher concentration of FeSO4, without compromising sensory acceptability and avoiding consumer rejection.…”
Section: Innovations In Dairy Productsmentioning
confidence: 99%